Parameters of the fault planes for the Crimean Black Sea region by averaged mechanism of close earthquakes - L. A. Shumlyanskaya; V. Yu. Burmin (Геофизический журнал, 2016)
A modern field of stress of the Crimean Black Sea region was constructed. A method of averaged mechanisms was used to construct the field of stress, which uses the earthquakes of varying intensity, including weak ones that prevail in the region. The research allowed allocating 15 blocks in the areas with different pairs of forces compression-stretching. It has been shown that nodal plane, formed under the influence of these forces describes the planes of rupture of tectonically active faults. Types of movements within the faults, which occur in the Crimean Black Sea region, were found. It has been shown that the faults and types of movements along them are related to the relief of Moho surface, and subcrustal mantle is a source of movement into the faults. Non-double-dipole model of the source of stresses was used to solve averaged mechanism. It makes possible to show that the Yalta-Alushta seismo-focal zone was formed by rotating the surrounding blocks counterclockwise. The axis of rotation corresponds to cross-section of the Salgir-Oktyabr’ and Orehovo-Pavlograd faults.